Efficacy and safety of narrowband ultraviolet B phototherapy for prurigo nodularis: a tertiary center experience - Esra Agaoglu; Hilal Kaya Erdogan; Ersoy Acer; Zeynep Nurhan Saracoglu (Anais Brasileiros de Dermatologia)
Abstract Background: Prurigo nodularis is a chronic pruritic dermatosis and narrowband-UVB (NB-UVB) phototherapy is considered an effective and safe treatment option in patients with multiple comorbidities. Objective: In this study, the authors aimed to evaluate the efficacy and safety of NB-UVB phototherapy in the management of prurigo nodularis and to compare response rates according to lesions localization. Methods: Thirty prurigo nodularis patients who had been treated with NB-UVB phototherapy were included in this study. The data for this study were retrieved retrospectively from patient follow-up forms in the phototherapy unit. Results: NB-UVB phototherapy led to a complete response (CR) in 24 (80%) patients while partial response (PR) was achieved in 6 (20%) patients. Regarding prurigo nodularis localization, the CR rate was statistically higher in those with diffuse and central involvement (p < 0.05). Erythema and/or pruritus were observed in 4 (13.3%) patients with prurigo nodularis. Study limitations: This study is limited because it is single-centered and has a retrospective design. Conclusions: NB-UVB phototherapy is an effective and safe treatment option for prurigo nodularis patients especially those with multiple comorbidities and using several medications. Patients with diffuse and central involvement may respond better to phototherapy than those with peripheral involvement.